The Result of Studentâs Process Skills Through the Implementation of Gas Kinetic Theory Learning Media Based on Inquiry Approach - Fitriana, Dea; Zulhelmi, Zulhelmi; Z, Fakhruddin (Proceedings of the UR International Conference on Educational Sciences, 2018)
This study aims to determine the learning outcomes of students process skills through the implementation of gas kinetic theory learning media based on the inquiry approach. The method that what used in this research is One Shot Case Study design. The subject of this research is class XI MIA 3 SMANegeri4Pekanbaru. An Instrument of the data collection wastest ofthe learning result of learning processskills. The data analysis technique used was descriptive analysis.The results showed the average absorption capacity of students process skills was in a good category at 74,95%. The level of process skills shows 81,25% of students have good basic skills, while the integrated skills are68,75%.It can be concluded that the implementation of learning media in the form of experimental devices based on the inquiry approach can improve the learning outcomes of studentâs process skills in the material of the kinetic theory of gas.